Gossip' in Organizational Communication Between Nurse, Doctor and Dentist Academicians - Serap Altuntaş; Özlem Şahin Altun; Rahşan Çevik Akyıl (Association of Nurse Managers, 2017)
INTRODUCTION: Although gossip is ignored or seen as unimportant, efforts are still made to prevent it, but it is cannot be eliminated entirely even in the best organizations. It is important that managers should manage gossip to maximize its positive effects, by controlling it, rather than trying to suppress it. This descriptive study was conducted to determine whether the gossip used in organizational communication by academicians. METHODS: This research was conducted with nursing, dentistry and medicine academicians that offers education about human health at a public university (n=177). A survey form developed by the researchers after a review of the literature was used for data collection. The ethics committee's consent and written official permissions were obtained for the study. The data were analyzed using frequency and percentage distribution tests and Statistical Package for the Social Sciences 22.0 software. RESULTS: The data analysis determined that academicians generally gossip about working conditions and to share information. They gossip with their friends, when they feel angry, and they do so face to face. It was also determined that they feel remorse and internal stress and try not to gossip again, yet their stress levels fall, their self-confidences increases and they feel relieved after they gossip. DISCUSSION AND CONCLUSION: Findings showed that the rate of use of that health education academics rumors appeared to be low.